Comparative analysis of barrier properties of BaCeO3 ceramics - Vinokurov, AL; Shlyakhtin, OA; Oh, YJ; Orlov, AV; Tretyakov, YD (IOP PUBLISHING LTD, 2003)
In order to study chemical resistance to the Y-Ba-Cu-O melts, dense BaCeO3 ceramics have been obtained from coprecipitated oxalate precursors using CuO and BaCuO2 sintering aids. BaZrO3 ceramics obtained in a similar way were used for comparison. SEM and EDX investigation of ceramic BaCeO3 after 12 h contact with molten cuprates at 1020 degreesC demonstrated no traces of macroscopic Ce dissolution or grain boundary corrosion. Nanoprobe EDX analysis of both ceramics detected no Cu within the BaCeO3 and BaZrO3 grains. Trace amounts of Ce and Zr were observed in several intergrain necks of frozen cuprate melt. Barrier properties of BaCeO3 (BaZrO3) materials can be further enhanced by surface plasma processing of presintered porous ceramics resulting in the formation of a molten crack-free layer, stable both to chemical corrosion and to physical penetration of the melt.
Keywords: YBCO SINGLE-CRYSTALS; BAZRO3; GROWTH; YBA2CU3O7-X; CRUCIBLES; MELT